(untitled) (University of Khartoum Journal of Agricultural Sciences, 2023)
Field experiments were conducted at Owo in the forest-savanna transition zone of southwestern Nigeria during 2007 and 2008cropping seasons to study the effect of different levels of poultry manure(0, 10, 20, 30 and 40 t/ha) on soil fertility, leaf nutrient content, growthand tuber yield of two species of yam; namely, white yam (Dioscorearotundata Poir) and yellow yam (Dioscorea cayenensis Lam). Thetreatments were factorially arranged in a randomized block design withthree replications. The soil was deficient in organic matter (OM), total N,available P, exchangeable K, Ca and Mg. The results showed that poultrymanure increased soil and leaf N, P, K, Ca and Mg, and soil OM, growthand tuber yield of the yams compared with the control treatments. Whiteyam produced significantly higher yield than yellow yam. Compared withyellow yam, white yam increased tuber yield by 19%, 26%, 36%, 3% and12%, respectively, for 0, 10, 20, 30 and 40 t/ha poultry manure.Application of poultry manure at 20 t/ha and 30 t/ha significantlyimproved growth and tuber yield of white yam and yellow yam,respectively, compared with the other treatments. These levels of poultrymanure are, therefore, recommended for the two yam species in forest-savanna transition zone of southwest Nigeria. Recommendations ofmanure for yam production should be variety specific.